Surgical site infection in cesarean sections with the use of a plastic sheath wound retractor compared to the traditional self-retaining metal retractor. (August 2016) - Hinkson, Larry; Siedentopf, Jan-Peter; Weichert, Alexander; Henrich, Wolfgang
Abstract: Objective: A cesarean section rate of up to 19.4% is reported worldwide. Surgical site infection occurs with rates of up to 13.5%. Plastic-sheath wound retractors show reduced rates of surgical site infections in abdominal surgery. There is limited evidence in women having cesarean sections. This study evaluates the use of the Alexis ® O C-Section Retractor in the prevention of surgical site infection in patients undergoing their first planned cesarean section compared to the traditional Collins self-retaining metal retractor. Study design: A single center, prospective, randomized, controlled, observational trial. The primary outcome is surgical site infection as defined by the Centers for Disease Control and Prevention. The secondary outcomes included intraoperative surgical parameters, postoperative pain scores and the short and long-term satisfaction with wound healing. From October 2013 to December 2015 at the Charité University Hospital, Berlin. 98 patients to the Alexis ® O C-Section Retractor group and 100 to the traditional Collins self-retaining metal retractor group. Results: A statistically significant reduction in the rate of surgical site infections, when the Alexis ® O C-Section Retractor was used for wound retraction compared to the traditional Collins metal self-retaining wound retractor, 1% vs. 8% (RR 7.84, 95% CI (2.45–70.71) p = 0.035). Conclusions: The use of plastic-sheath wound retractors compared to the traditional self-retaining metal retractor in low risk women, having the first cesarean section is associated with a significantly reduced risk of surgical site infection.